Beyond Pippi Longstocking: Intermedial and International Aspects of Astrid Lindgren’s Works. Ed. Bettina Kümmerling-Meibauer and Astrid Surmatz - Pia Maria Ahlbäck (Barnboken: Tidskrift för Barnlitteraturforskning, 2012)
Review/recension